CALCIUM CHLORATE IS BASED ON SODIUM CHLORATE AND CALCIUM CHLORATE STUDY OF WATER SYSTEMS - Omonbayeva Gulzoda Botirjon qizi (American Journals Publishing, 2023)
In this regard, we studied this system in a very political-political way. Liquidity lines of ice and calcium chlorate with different levels of hydration were determined in the water solubility curve of calcium chlorate. In the solubility curve of the calcium chlorate–water system, ice formation continues to 46.1% of calcium chlorate at -40.300C (eutectic). From this point, calcium chlorate hexahydrate, stable to -27.2°C, crystallizes. The temperature range of -27.2°C -6.8°C corresponds to the crystallization zone of tetrahydrous calcium chlorate.
Keywords: Bischofite, calcium-magnesium chlorate, solubility, diagram, binary systems, ice, crystallize, sodium chlorate.